Neighborhood socioeconomic status and risk of hospitalization in patients with chronic kidney disease: A chronic renal insufficiency cohort study. Issue 28 (10th July 2020) - Saunders, Milda R.; Ricardo, Ana C.; Chen, Jinsong; Anderson, Amanda H.; Cedillo-Couvert, Esteban A.; Fischer, Michael J.; Hernandez-Rivera, Jesus; Hicken, Margaret T.; Hsu, Jesse Y.; Zhang, Xiaoming; Hynes, Denise; Jaar, Bernard; et al.
Abstract : Abstract: Patients with chronic kidney disease (CKD) experience significantly greater morbidity than the general population. The hospitalization rate for patients with CKD is significantly higher than the general population. The extent to which neighborhood-level socioeconomic status (SES) is associated with hospitalization has been less explored, both in the general population and among those with CKD. We evaluated the relationship between neighborhood SES and hospitalizations for adults with CKD participating in the Chronic Renal Insufficiency Cohort Study. Neighborhood SES quartiles were created utilizing a validated neighborhood-level SES summary measure expressed as z-scores for 6 census-derived variables. The relationship between neighborhood SES and hospitalizations was examined using Poisson regression models after adjusting for demographic characteristics, individual SES, lifestyle, and clinical factors while taking into account clustering within clinical centers and census block groups. Among 3291 participants with neighborhood SES data, mean age was 58 years, 55% were male, 41% non-Hispanic white, 49% had diabetes, and mean estimated glomerular filtration rate (eGFR) was 44 ml/min/1.73 m 2 . In the fully adjusted model, compared to individuals in the highest SES neighborhood quartile, individuals in the lowest SES neighborhood quartile had higher risk for all-cause hospitalization (rate ratio [RR], 1.28, 95% CI, 1.09–1.51) and non-cardiovascular hospitalization (RR 1.30, 95% CI, 1.10–1.55). The association with cardiovascular hospitalization was in the same direction but not statistically significant (RR 1.21, 95% CI, 0.97–1.52). Neighborhood SES is associated with risk for hospitalization in individuals with CKD even after adjusting for individual SES, lifestyle, and clinical factors. Abstract : Supplemental Digital Content is available in the text